2015 Spillover Report. (Policy Papers; Policy Paper ;, 2015)
Many countries around the globe, particularly the systemic advanced economies, face the challenge of closing output gaps and raising potential output growth. Addressing these challenges requires a package of macroeconomic, financial and structural policies that will boost both aggregate demand and aggregate supply, while closing the shortfall between demand and supply. Each element of this package is important and one cannot substitute for the other: easy monetary policy will not raise potential output just as structural reforms will not close the output gap. This report studies the impact on emerging markets and nonsystemic advanced economies from monetary policy actions in systemic advanced economies, with a look also at knock-on effects from the decline in world oil prices.